Acute toxicity and gastroprotective effect of the schiff base ligand 1H-indole-3-ethylene-5-nitrosalicylaldimine and its nickel (II) complex on ethanol induced gastric lesions in rats - Abdullah, M.A.; Ibrahim, M.M.; Ali, Hapipah Mohd; Hassandarvish, P. (MDPI, 2012)
The present study was performed to evaluate the gastroprotective activity of Schiff base ligand derived from the condensation reaction of tryptamine (an indole derivative) and 5-nitrosalicylaldehyde (TNS) and its nickel (II) complex against ethanol-induced gastric ulcer in rats. The compounds were orally administered with low (30 mg/kg) and high (60 mg/kg) doses to ulcer-induced Sprague-Dawley rats.Macroscopically, the ulcer control group exhibited severe mucosal injury, whereas pre-treatment with either cimetidine or TNS and its nickel (II) complex each resulted in significant protection against gastric mucosal injury. Flattening of gastric mucosal folds was also observed in rats pretreated with TNS and its nickel complex. Histological studies of the gastric wall of ulcer control group revealed severe damage of gastric mucosa, along with edema and leucocytes infiltration of the submucosal layer compared to rats pre-treated with either cimetidine or TNS and its nickel (II) compound, where there was marked gastric protection along with reduction of edema and leucocytes infiltration of the submucosal layer. Acute toxicity study done on mice with a higher dose of 5 g/kg of TNS and its nickel (II) complex did not manifest any toxicological signs. Research finding suggest that TNS and its nickel (II) complex could be considered as effective gastroprotective compounds.